Discourses of a doubtful city: traditionalism and Modernity in the 1920’s Recife - Silva, Luiz Vinícius Maciel (Em Perspectiva, 2019)
The main objective of this work was to analyze the debate promoted by the priest and the oratorian philosopher Teodoro de Almeida (1722-1804) about the diffusion of the books of some French thinkers in the scope of his parenética. The ethical and moral question within the thought of this important Portuguese thinker of the Enlightenment era was much investigated in historiography, which has been more fully studied in the last volumes of his great work, Philosophical Recreation. However, our study attempted to show that the clash held by the clergy against modern moral philosophy represented by philosophers such as Voltaire, Rousseau, and Marmontel, took a great deal of emphasis in the pulpit as well, and for this we have analyzed one of his sermons preached in 1778 or 1779 and published in 1787, therefore prior to the publication of the abovementioned volumes of Philosophical Recreation. Reading this sermon allows us to verify how an important agent of eighteenth-century Portuguese literary culture reflected on the diffusion of such ideas at that time.